The Role of Organizational Commitment as a Mediation of The Influence of Principal Leadership on The Performance of Leading Teachers in Acceleration of The Implementation of The Independent Curriculum - Putu Pande Hari Sugi Bali; A. A. Ngurah Gede Sadiartha; Ida I Dewa Ayu Yayati Wilyadewi (Journal of Sustainable Development Science, 2026)
This study seeks to investigate and explain the impact of principal leadership on the performance of driving teachers in North Konawe Regency, as mediated by organizational commitment. The strategy to this study is a survey that uses an explanatory research design. Data was collected cross-sectionally using a questionnaire. This study's population consisted of all driving teachers working in North Konawe Regency, which totaled 34 people. The sampling approach utilized in this study was a saturated sample, which is a sampling strategy that uses all members of the community as samples. This study's hypothesis was tested using the partial least squares (PLS) analysis method. The findings indicated that principle leadership had a favorable and significant impact on the performance of driving teachers. The principal's leadership had a major and positive impact on organizational dedication. Furthermore, organizational dedication had a good and significant impact on the performance of driving instructors. Organizational commitment has been shown to moderate the relationship between principal leadership and the performance of teachers. This study concludes that principal leadership has both a direct and indirect impact on the performance of driving teachers through organizational commitment. Based on the research findings, it is recommended that the main implement more supportive leadership, the school work environment is improved to strengthen the organizational commitment of teachers, and the allocation of time and support for the driving teacher in helping students is considered through training, workload management, and incentives. The implications of the research are that the respondents of this research are limited to the Driving Teachers in North Konawe Regency. As a result, it may limit the capacity to generalize the findings of this study, particularly to public organizations or agencies in different locations.